2018
DOI: 10.1080/13696998.2018.1478838
|View full text |Cite
|
Sign up to set email alerts
|

Clinical trials with multiple endpoints can establish a correlation, but not (yet) causality, between dietary supplementation with omega-3 fatty acids and keratoconjunctivitis sicca

Abstract: Comparability of omega-3 therapeutic efficacy and effectiveness remains a major challenge in dry eye disease management. Notwithstanding its multi-factorial character, addressing prevailing methodological and empirical issues in clinical trials will help reduce knowledge gaps and normative choices among eye physicians and patients alike. In this regard, pharmacoeconomics offers a useful and robust toolset through which analysis of cost-minimization, cost-effectiveness, and cost-utility as well as meta-analysis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 31 publications
0
10
0
Order By: Relevance
“…Dietary supplementation with omega-3 fatty acids (omega-3s) in keratoconjunctivitis sicca (colloquially known as dry eye disease) is illustrative of healthcare interventions in which patient comfort and relief from signs and symptoms are the anticipated primary gains in QoL. This contrasts with prescription drugs and medical devices for which QALYs are typically derived to adjust or correct life expectancy based on additional life years and levels of health-related QoL predicted for a patient in a given condition (Mendoza, 2018).…”
Section: Methodsmentioning
confidence: 99%
“…Dietary supplementation with omega-3 fatty acids (omega-3s) in keratoconjunctivitis sicca (colloquially known as dry eye disease) is illustrative of healthcare interventions in which patient comfort and relief from signs and symptoms are the anticipated primary gains in QoL. This contrasts with prescription drugs and medical devices for which QALYs are typically derived to adjust or correct life expectancy based on additional life years and levels of health-related QoL predicted for a patient in a given condition (Mendoza, 2018).…”
Section: Methodsmentioning
confidence: 99%
“…Evidence accumulated from studies conducted within the past decades indicates that supplementation with PUFAs, particularly ω3, may help the treatment of DED [85].…”
Section: Current Perspectivesmentioning
confidence: 99%
“…The daily intake of a moderate dose of ω3 was also shown to have beneficial effect against MGD [84]. Meanwhile, the safety profiles of PUFAs have not been paid much attention to, as studies regarding the PUFAs supplementation in patients with DED have rarely reported adverse effects of the PUFAs [85].…”
Section: Current Perspectivesmentioning
confidence: 99%
See 2 more Smart Citations